Application of value stream mapping for analysis and performance improvement of black glutinous rice supply chain - Janthawong, Y.; Wattanutchariya, W.; Tippayawong, K.Y. (Engineering and Applied Science Research, 2016)
Thailand has the largest area of glutinous rice plantation in ASEAN and is the top glutinous rice exporting country in the world. This research was aimed to investigate, analyze and propose improvement of a black glutinous rice supply chain. Value stream mapping analysis (VSM) was used to identify and categorize activities in the chain. ECRS technique (Eliminate, Combine, Rearrange and Simplify technique) was then used to improve performance of the supply chain. From the results obtained, it was shown that some activities might be eliminated, and total cycle time could be reduced by 20% and 7%, respectively. ECRS proved to be useful in shortening storage and delivery times, hence, cost reduction in the black glutinous rice supply chain. Farmers, rice milling operators, and rice cooperatives will gain several benefits and become more responsive in future customer demands.